USULAN EFISIENSI WASTE PROSES PRODUKSI BED SHEET DI PT. ABC MENGGUNAKAN METODE VALUE STREAM MAPPING - Dandi Nurdiansyah; Sarah Nur Fatimah; Hani Nurwiyanti; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
Smooth production is very important to achieve the targets to be achieved by producers efficiently. This is also done at PT. ABC which produces various products in the form of bed linen. In the production process PT. ABC still has many production processes that consume a lot of production time (waste), starting from the beginning of the work to the time of product delivery to the customer, especially the high process that experiences lead times, equipment and machines that do not meet production capacity. The purpose of this study is to provide suggestions for improvement in reducing waste that occurs at PT. ABC This research method is a value stream mapping (VSM) which will map the value of each activity in each production process that occurs. It aims to determine which activities provide added value (value added) and which do not provide added value (non-value added) and can provide suggestions. improvements to the future state map to reduce time waste that occurs in the production process activity of the door panel box 7. The results of the approach using the value stream mapping tool and applying the proposed improvements, where the analysis compares the analysis of the current state map with the future state map. The results of this study get the results of the current state map analysis for value added activities of 499.8 seconds and non-value-added activities of 801.27 seconds